The political relationship between the State and the economic groups from the industrial sector during the first government of Carlos Menem in Argentina (1989-1995) - Fair, Hernán (Sociedad y Economía, 2010)
During the government of Carlos Menem was carried out a structural transformation process that has deepened in the implementation of a model of pro-market accumulation started in the mid 70s. From a global macroeconomic framework, focusing upon theoretical approach discursive matrix, the overall objective of this paper consist to analyze the political relationship established between the State and the economic groups linked to the industrial sector. More specifically, it is proposed to investigate about the diverse modalitiesof state intervention and its correlative effects on the ideological and socio-economic transformation of the industrial business leaders during the menemism first government (1989-1995), trying to elucidate its relationship with the process of political legitimacy to the neoliberal reforms carried out during that stage.